Optimal Design and Sensitivity Analysis of Roof Truss - Chetchotisak, Panatchai (Engineering and Applied Science Research, 2012)
This paper presented an optimal design and sensitivity analysis of roof truss structures. Theobjective function was the weight of the roof truss, expressed as the weight of cords, webs and diagonalmembers. The seven design variables were taken into the formulation. The Timoshenko beam model was usedto determine stress and deflection of the roof truss in terms of a closed form solution. Sixteen non-linearconstrain equations were formulated according to AISC-89 code requirements. The solution was carried outby the MATHCAD program. An illustrative problem was solved, and its results were presented and discussed.Finally the sensitivity analysis was included for selection of the design parameters.